Verb agreement in Brazilian Sign Language: morphophonology, syntax & semantics - Guilherme Lourenco de Souza (2018)
Building on the assumption that signed languages are both similar and different from spoken languages (universal principles vs. modality effects), this dissertation discusses verb agreement in Brazilian Sign Language (Libras). Agreement in sign languages has been described as a change in orientation and direction of movement of the verb. However, I propose that agreement in Libras, and possibly in all sign languages, is not marked by the movement of the verb. Instead, the matching of location between the verb and its argument(s) is the sole agreement marker a process I will call co-localization. The different types of path movement, on the other hand, are related to the event properties of the predicate, such as marking of telicity, for example (Event Visibility Hypothesis). Additionally, assuming a Minimalist framework within Generative Syntax, I will claim that the different agreement patterns found in Libras can be derived by assuming a single underlying syntactic structure and by the basic syntactic operations MERGE and AGREE. Finally, I will argue that there is a layering of visual information within the verb internal structure, in such a way that different morphological operations will target specific nodes of the phonological specification of the verb.